2013
DOI: 10.1016/j.otsr.2013.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Peroneal nerve entrapment at the fibular head: Outcomes of neurolysis

Abstract: Level IV, retrospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 6 publications
0
70
0
1
Order By: Relevance
“…In 0-67% of operated PTEN patients no identifiable cause of their PN neuropathy could be found. [1][2][3][4] Similarly, the cause of PNEN in our patient was unknown although it produced severe intermittent claudication. Based on our observations, we suggest that in the absence of an obvious inciting event eliciting PN dysfunction, PNEN should be considered in patients with intermittent claudication.…”
Section: B Amentioning
confidence: 66%
See 3 more Smart Citations
“…In 0-67% of operated PTEN patients no identifiable cause of their PN neuropathy could be found. [1][2][3][4] Similarly, the cause of PNEN in our patient was unknown although it produced severe intermittent claudication. Based on our observations, we suggest that in the absence of an obvious inciting event eliciting PN dysfunction, PNEN should be considered in patients with intermittent claudication.…”
Section: B Amentioning
confidence: 66%
“…3) Maalla et al 2) reported that in their PN decompression surgery series, half of their patients suffered only isolated sensory dysfunction while others manifested both sensory and motor dysfunction. The Tinel sign over the fibular head suggests PN compression and may warrant PN decompression surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, the prognosis for a demyelinating lesion is much more favorable than for an axonal loss lesion [13]. The outcome is usually favorable if surgery is done within four months after first presentation of neurological deficits, and less favorable in patients who have neurological symptoms for longer than one year [1,14]. For irreparable CPN palsy, a tendon transfer procedure utilizing the tibialis posterior, first described in 1933 by Ober [15], with or without a combined transfer of the flexor digitorum longus is the method of choice for functional recovery of patients (Figure 2A-C) [16,17].…”
Section: Wwwijcasereportsandimagescommentioning
confidence: 99%